THE EFFECT OF BREASTFEEDING ON THE MAXILLOFACIAL AREA (CAHIERS MAGELLANES-NS, 2024)
: Breastfeeding is an unparalleled way to provide infants with ideal nutrition for their full growth and development. Natural feeding has a biological advantage over artificial feeding and ensures the correct and full development of the child. Lack or insufficient breastfeeding can lead to the development of dysbacteriosis, contribute to the occurrence of periodontal and dental diseases, and negatively affect digestion. In recent years, there has been a worldwide trend towards replacing natural feeding with artificial feeding. This leads to a very common pathology of the maxillofacial region in the form of a violation of the formation of the dentoalveolar system, the absence of three and subsequent crowded teething, which violates the aesthetic appearance of the patient and affects the digestive system and nutritional status (a set of clinical, anthropometric and laboratory indicators that characterize the quantitative ratio of muscle and fat body mass) of the child.Purpose: Optimization of methods for the prevention of dental diseases in children, taking into account the type of feeding at an early age.Materials and methods: To study the significance of risk factors for the development of dental diseases in children, depending on the type of feeding in early childhood, a survey and an objective dental examination of 1066 preschool children organized in preschool institutions in the Bukhara region were conducted. 170 children were selected for the study, of which 140 were children with various dental diseases and 30 healthy children with a normal dental status.Results: Among 357 children who were bottle-fed, 54 had dentoalveolar anomalies (71.8%) In addition, they had bad habits of one kind or another. In our study, the results of a dental examination of preschool children revealed a significantly low oral hygiene index in the 2nd group of children who were on artificial mixed feeding 2.6 ± 0.07 (P < 0.01) compared to the control group ±0.07. The indicators of the 3-group were at the level of control values 1.18±0.02 without significant statistical differences.Conclusion: The obtained data on the assessment of dental status showed the importance of taking into account the type of feeding at an early age when examining and drawing up a plan for the prevention of dental diseases among preschool children.